Strategi Pelaksanaan Intervensi Gizi Spesifik dalam Rangka Percepatan Penurunan Kondisi Stunting - Jamaluddin, Jamaluddin; Samsuddin, Samsuddin; Fauzi, Andika (Badan Riset dan Inovasi Daerah Kabupaten Pelalawan, 2023)
Stunting is a chronic nutritional problem caused by a lack of nutrition in the long term, resulting in disruption of growth and development in children. Stunting is also one of the causes of stunted children's height, so that it is lower than children of their age. The purpose of this study is how to carry out appropriate nutrition interventions for toddlers who are likely to experience stunting in Pelalawan Regency and what can be done to prevent stunting in toddlers from an early age. The research study carried out in this study is a literature study or the materials needed in this study come from data that has reliable sources and can be proven valid. Journal taken from ProQuest in 2012-2022. The findings from this study are that the way to carry out nutritional interventions for toddlers who are likely to experience stunting is to carry out nutritional assessments, nutrition diagnoses, nutritional interventions and nutritional monitoring and evaluation. Things that can be done to prevent stunting in toddlers are to pay attention to the condition and adequacy of nutrition that enters the mother's body during pregnancy and breastfeeding, exclusive breastfeeding until the baby reaches the age of 6 months, accompanying breastfeeding with healthy complementary foods and carrying out health monitoring of babies who are newborn to enter the age of 1,000 days of life in the world.